EVALUATION ON THE ANEMIA THERAPY USAGE TOWARD CHRONIC KIDNEY DISEASE ASKES PATIENTS RECEIVING REGULAR HAEMODIALYSIS THERAPY AT PKU MUHAMMADIYAH HOSPITAL YOGYAKARTA - Hidayati Hidayati; Agung Endro Nugroho; Inayati Inayati (Faculty of Pharmacy, Universitas Gadjah Mada)
Anemia is mostly associated with chronic kidney disease (CKD) patients. Anemia in CKD patients occurs due to the lack of erythropoietin. Low hemoglobin concentration relates to bad clinic outcome toward CKD patients. Epoetin therapy for CKD patients has been clinically confirmed to improve the quality of life and lower the morbidity and mortality rate. This research was intended to investigate the anemia profile therapy, adjuvant per-oral anemia therapy adherence profile and the effect of adjuvant per-oral anemia therapy adherence toward achievement target of anemia therapy using epoetin in CKD Askes patient receiving regular haemodialysis therapy at PKU Muhammadiyah Hospital Yogyakarta. The research was conducted using observational study design with prospective data collection, then the data were analyzed in order to know the success of anemia primary therapy via epoetin and adjuvant per-oral anemia therapy. The success of therapy were measured based on National Kidney Foundation-Kidney Disease Outcomes Quality Initiative (NKF-K/DOQI), 2006, while adherence was measured via Modified Morisky Scale (MMS) questionnaire. Based on the research, epoetin used in this research was epoetin alpha and beta, each 69.05% and 30.95%. Adjuvant per-oral anemia therapy used in this research was combined folic acid, iron and vitamin B complex (82.05%); folic acid (10.26%); combined folic acid and vitamin B-complex (7.69%). Groups of epoetin sub dose with unachieved target and epoetin complete dose with unachieved target were 64.29% and 21.41%; Groups of epoetin sub dose with achieved target and epoetin complete dose with achieved target showed similar results 7.14%. The adherence profile of adjuvant per-oral anemia therapy were consisted of obedient patients and disobedient patients, each 69.23% and 30.77%. Askespatient adherence in using adjuvant per-oral anemia therapy, in this research, was able to assist the achievement of epoetin therapy target. Keywords : Anemia, adherence, chronic kidney disease, regular haemodialysis, epoetin, adjuvant per-oral anemia